2003
DOI: 10.1038/sj.bdj.4809930
|View full text |Cite
|
Sign up to set email alerts
|

Changes in life quality following third molar surgery – the immediate postoperative period

Abstract: Objectives This study describes patients' perceptions of changes in oral health related quality of life (OHQOL) in the early postoperative period following third molar surgery. Methods One hundred patients were enrolled in a prospective cohort study of the surgical removal of lower third molars under local anaesthetic. Two specific oral health related quality of life measures, OHIP-14 and OHQoLUK© were administered to the study group prior to surgery. Standardized surgical and analgesic protocols were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 15 publications
9
113
1
9
Order By: Relevance
“…In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared. We observed that trismus was severe on day 2 in all groups and decreased on day 7, consistent with the results of other studies in the literature (17)(18)(19)(20)(21)(22). Similarly, no statistically significant difference was found between groups in edema at postoperative 2 and 7 days.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared. We observed that trismus was severe on day 2 in all groups and decreased on day 7, consistent with the results of other studies in the literature (17)(18)(19)(20)(21)(22). Similarly, no statistically significant difference was found between groups in edema at postoperative 2 and 7 days.…”
Section: Discussionsupporting
confidence: 82%
“…Trismus reaches its maximum level 2 days after extraction and may last for 7-10 days (21). It has been claimed that the duration and severity of this complication varies from patient to patient (17)(18)(19)(20)(21). In our study, there was no statistically significant difference between groups when the levels of trismus at postoperative 2 and 7 days were compared.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Frequently, this is a short-lasting and moderate pain, reaching its maximum intensity within a short period of time after the end of surgery, and, in most cases, patients require some kind of analgesic to treat it (1). Besides pain, swelling and mouth opening limitation associated with the inflammatory response are also undesirable consequences for patients who undergo surgical interventions in the oral cavity (2).…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons in the UK every year (6). The surgical procedure causes acute pain, swelling and limited mouth opening.…”
Section: M3m Removal Is the Most Commonly Performed Procedures By Oralmentioning
confidence: 99%